Pengaruh Promosi Melalui WhatsApp Terhadap Minat Beli Konsumen Pada Produk UMKM di Kelurahan Bangsri - Ulya, Himmatul; Astuti, Tri Rahayu Puji (Universitas Mitra Indonesia, 2025)
The purpose of this research is to find out whether promotion via WhatsApp affects consumer buying interest in MSME products in Bangsri Village. It was researched using quantitative methods with purposive sampling techniques involving 100 respondents according to the criteria in Bangsri Village. Data was obtained from distributing questionnaires and analyzed using the simple linear regression method. The results showed that promotion through WhatsApp has a positive and significant effect on consumer buying interest, with a beta coefficient value of 0.834 and a significance value of p = 0.001. This finding shows that the more intensive the promotion through WhatsApp, the more intensive the consumer's buying interest. Thus, promotion through WhatsApp is effective to be used as a digital marketing strategy for MSME players. Keywords: promotion, WhatsApp, purchase intention, MSMEs, simple linear regression